Acid phosphatase polypeptides in Saccharomyces cerevisiae are encoded by a differentially regulated multigene family. - Rogers, D T (1982)
Two clones from a lambda phage collection containing yeast genes regulated by inorganic phosphate were shown by low-stringency hybridization to select three mRNAs that direct the in vitro synthesis of repressible acid phosphatase (EC 3.1.3.2) polypeptides p60, p58, and p56. By higher stringency hybridization one yeast fragment [8 kilobases (kb)] selects p60 mRNA and the other (5 kb) selects p56 mRNA. These EcoRI digestion fragments were subcloned in yeast transformation vectors and hybridization selection assignments were confirmed by measuring enzyme and mRNA levels in transformants. Enzyme and mRNA levels in (8-kb) high copy number transformants grown in high inorganic phosphate medium revealed a hitherto undetected acid phosphatase protein, P57, which is believed to correspond to the constitutive enzyme encoded by PHO3. The identify of the 8-kb fragment purported to contain the PHO5/PHO3 genes was confirmed by genetic mapping of an integrated copy of this fragment. The site of integration of the 5-kb fragment was demonstrated to be unlinked to the PHO5/PHO3 genes.